2023
DOI: 10.1039/d2dt03362c
|View full text |Cite
|
Sign up to set email alerts
|

Flexible three-dimensional diacetylene functionalized covalent organic frameworks for efficient iodine capture

Abstract: The construction of functionalized covalent organic frameworks (COFs) is of great significance for broadening their potential applications, but are yet challenging to achieve, especially to three-dimensional (3D) COFs, because the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In conclusion, the insertion of acetylenes from TMT-TFPB-COF to TMT-TFPEB-COF eliminates the steric effect and provides more delocalized π-electrons, inducing extended visible-light absorption, high charge mobility, and suppressed charge recombination. The superiority of acetylene groups in extending visible-light response and suppressing charge recombination rate has been revealed. It seems that the insertion of diacetylene could induce more considerable promotion of the optical properties of COFs. , Here, the insertion of diacetylenes into TMT-TFPB-COF was attempted to further explore the effect of expanding the π-conjugation on the photocatalytic performance. However, these endeavors were fruitless in affording crystalline materials, even after dozens of attempts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In conclusion, the insertion of acetylenes from TMT-TFPB-COF to TMT-TFPEB-COF eliminates the steric effect and provides more delocalized π-electrons, inducing extended visible-light absorption, high charge mobility, and suppressed charge recombination. The superiority of acetylene groups in extending visible-light response and suppressing charge recombination rate has been revealed. It seems that the insertion of diacetylene could induce more considerable promotion of the optical properties of COFs. , Here, the insertion of diacetylenes into TMT-TFPB-COF was attempted to further explore the effect of expanding the π-conjugation on the photocatalytic performance. However, these endeavors were fruitless in affording crystalline materials, even after dozens of attempts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Zhao et al reported that CPOF-2 and CPOF-3 functionalized with electron-rich acetylene and diacetylene groups exhibited high adsorption capacities of 5.40 and 5.87 g g −1 , respectively. 89 Fang et al also demonstrated a strong interaction between tetrathiafulvalene (TTF) and I 2 in JUC-561 with an excellent uptake of 8.19 g g −1 . 90…”
Section: Gas Storagementioning
confidence: 98%
“…13 C NMR (126 MHz, CDCl 3 ):  = 93.3, 90.1, -0.2. 70 Yield: 160 mg (81%); pale yellow solid; mp 119-120 °C. R f = 0.44 (20% EtOAc/n-hexane).…”
Section: 4′-(buta-13-diyne-14-diyl)bis(nn-dimethylaniline) (2h)mentioning
confidence: 99%
“…4′-(Buta-1,3-diyne-1,4-diyl)dibenzaldehyde (2o)70 Yield: 160 mg (81%); pale yellow solid; mp 119-120 °C. R f = 0.44 (20% EtOAc/n-hexane).…”
mentioning
confidence: 99%